Ideology and Structure in Giardinelli's Santo Oficio de la memoria - Gustavo Pellón (Studies in 20th & 21st Century Literature, 1995)
The article studies the most recent novel by Argentine novelist Mempo Giardinelli from the point of view of its polyphonic structure. Santo Oficio is compared to one of its models, William Faulkner's As I Lay Dying, and the respective modern and postmodern aesthetics ofboth novels are discussed. Giardinelli's approach in this ambitious novel is contrasted with that of major authors of the Latin American Boom. A family tree of the Domeniconelle family, the protagonists of Santo Oficio, is included.
Keywords: Santo oficio de la memoria; Giardinelli; As I Lay Dying; William Faulkner; Argentine literature; novel